Reaction of [60]fullerene with morpholine and piperidine: Preferred 1,4-additions and fullerene dimer formation - Schick, Georg; Kampe, Klaus-Dieter; Hirsch, Andreas (Journal of the Chemical Society - Series Chemical Communications, 1995)
Reactions of an excess of secondary amines with benzene solutions of [60]fullerene in the presence of oxygen lead to dehydrogenated bisadducts and tetraadduct epoxides with a defined 1,4-addition pattern of the amino groups as well as to the first example of an aminated fullerene dimer.